Improving Reading Comprehension Skills Using Collaborative Reading and Alternative Text Strategies for VIIIA Class Students in SMPQ An-Nawawiy Mojokerto - Lus Firdaus Zakiya; Lina Rihatul hima (Kirana Publisher (KNPub), 2023)
This research study aims to describe the improvement of reading comprehension skills of class VIII A students of SMPQ An-Nawawiy Mojokerto by using Collaborative Reading and Alternative Text strategies.The type of this research study was Classroom Action Research. The study subjects were students of class VIII A SMPQ An-Nawawiy Mojokerto, amounting to 34 students. This research was conducted in two cycles which in each cycle there were four components, namely planning, action, observation, and reflection. The object of this study was reading comprehension skills of students of class VIII A SMPQ An-Nawawiy Mojokerto. The technique of data collection included field notes, objects / observations, interviews, documentation, and tests. And the technique of data analysis was descriptive qualitative analysis technique. The results showed that the strategy of Collaborative Reading and Alternative Text can improve students reading comprehension skills of class VIII A SMPQ An-Nawawiy Mojokerto. The improvement of students’ reading comprehension skill was based on product quality and process quality. The quality improvement of the learning process can be seen from students that become more active, enthusiastic, and students were also always working with other friends while solving problems to be done in groups. Improved process ultimately has a positive impact on product quality improvement. The improvement of product quality learners were seen from student learning outcomes. Based on the results of pre-action testing conducted, students' reading comprehension ability obtained an average of 64. After being given action in cycle I, the average score of students reading comprehension ability become 68.88. It increases 4.10 points. Then in cycle II, the average score becomes 81.91. These results indicate that this research can be said to be successful because the average value of students' reading comprehension ability increases compared with pre-action values.